Challenges Encountered by Mathematics Teachers in ICTs Implementation - Parajuli, Kharika Devi; Koirala, Bidhya Nath (JMC Research Journal, 2021)
Information and communication technologies (ICT) have a great deal with teaching and learning processes to conceptualize abstract concepts in mathematics. The objective of this study investigated the challenges encountered by secondary-level mathematics teachers while implementing ICT-based training in a classroom in teaching. We used interpretive inquiry as an approach to research. As the study tools, we used in-depth interviews, observations, and generated textual data. We analyzed the data by adopting the data's sequential coding, categorizing, and thematizing. We used constructivism as a theoretical lens to understand and explore the use of ICTs. We envisaged and generated the themes on challenges that are inadequate ICT-based professional development training and tools; lack of competency in technological/ pedagogical content knowledge; disempowering school actors; enduring 'one size fits for all'; structured curriculum; lack of infrastructure and ICT tools and hegemony of traditional classroom practices. The significance of the use of ICTs has been recognized in public schools in Nepal. There was also evidence that the current practice of ICT-based teacher education and development was not excess in developing skills and knowledge to use ICT in their classroom.